PELATIHAN KADER REMAJA DALAM MENINGKATKAN KESEHATAN MENTAL - Ekayani, Ni Wayan Diana; Indiani, Ni Luh Putu; Ekayanti, Ni Wayan Sri; Wijaya, Putu Austin Widyasari; Evayanti, Luh Gde; Putra, Adi Pratama (UNHI Press, 2025)
Adolescents are vulnerable to stress that can cause behavioral disorders, mental health problems, and self-harm. They undergo many changes physically, psychologically, and socially. The Community Partnership Development Team of the Faculty of Medicine and Health Sciences of Universitas Warmadewa trained adolescent cadres at one of the high schools as part of student empowerment in improving mental health. The training began with material on mental health disorders and self-management, discussion, and a post-test. Thirty participants attended the activity, but only 22 people completed it. The participants comprised 14 women (63.6%) and eight men (36.4%). There were six people (27.3%) who had experienced mental health problems. The mean of the post-test questions was 85.45. This evaluation showed that the participants' understanding of the topic was quite good. The trained youth cadres are expected to help conduct early detection of mental disorders and provide simple counseling to other students. Cooperation between schools and students needs to continue to increase awareness of the importance of adolescent mental health.